A novel and green preparation of porous forsterite ceramics with excellent thermal isolation properties. Issue 3 (15th February 2019) - Zhao, Fei; Zhang, Lixin; Ren, Zhen; Gao, Jinxing; Chen, Xiaoyu; Liu, Xinhong; Ge, Tiezhu
Abstract: This work provides a novel and green approach to preparing porous forsterite ceramics by a transient liquid phase diffusion process based on fused magnesia and quartz powders without detrimental additives. The size of quartz particles markedly affected the sintering behaviors, phase composition, microstructure and properties of the porous forsterite ceramics. Fine quartz particles (D50, 3.87 µm) accelerated the rate of the forsterite formation at elevated temperatures and promoted solid-state sintering behavior of the porous ceramics. Conversely, coarse quartz particles (D50, 25.38 µm) reduced the rate of the solid state reaction and a large amount of unreacted SiO2 and enstatite (MgSiO3 ) phases transformed into a transient liquid-phase during the firing process. This effect resulted in a high porosity (approximately 58.89%) and formation of many large pores (mean pore size of 42.36 µm). These features contributed to the excellent thermal isolation properties of the prepared porous forsterite ceramics. The strength of the obtained porous ceramics (about 23.6 MPa) is relatively high compared with those of conventional ceramics.